2019
DOI: 10.1002/ajoc.201900058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Evaluation of Cephalosporin Isosteres

Abstract: As part of a program to explore the chemistry of β-lactams and their derivatives, we prepared a focused set of benzazetidine, indoline, and indole heterocycles, as well as flexible unconstrained variations of the four-membered heterocyclic compounds. These analogues mimic the threedimensional shape of cephalosporins but are not prone to covalent binding via ring opening. Although these analogues were inactive against the ESKAPE pathogens and Mtb, they represent unique and underexplored chemotypes for future bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The synthetic procedures of these newly synthesized GPR52 agonists are depicted in Schemes – . As outlined in Scheme , intermediate 6 was prepared by reduction of starting material 5 with triethylsilane and trifluoroacetic acid . Intermediates 8a – c were generated by reaction of compound 6 with commercially available compounds 7a – c in the presence of Et 3 N in yields of 63–67% .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthetic procedures of these newly synthesized GPR52 agonists are depicted in Schemes – . As outlined in Scheme , intermediate 6 was prepared by reduction of starting material 5 with triethylsilane and trifluoroacetic acid . Intermediates 8a – c were generated by reaction of compound 6 with commercially available compounds 7a – c in the presence of Et 3 N in yields of 63–67% .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As outlined in Scheme 1, intermediate 6 was prepared by reduction of starting material 5 with triethylsilane and trifluoroacetic acid. 22 Intermediates 8a−c were generated by reaction of compound 6 with commercially available compounds 7a−c in the presence of Et 3 N in yields of 63− 67%. 23 Intermediates 10a−c were produced via nucleophilic substitution of compounds 8a−c with commercially available 2-(3-fluoro-5-(trifluoromethyl)phenyl)acetonitrile (9a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, several research groups have designed and created analogs that maintain the overall shape of classical cephalosporin but lack the electrophilic β‐lactam ring and therefore they are devoid of the acylating potential toward the serine residues of the target proteins . In a recent contribution, the authors reported the design, synthesis, and study of the biological activity as antibacterials of various compounds, from indoles, indolines, and acyl amides to highly strained benzazetidines . In this regard, the development of new synthetic approaches for the preparation of this class of heterocycles may open new paths to pharmaceutically active antibacterial agents acting as bioisosteres of β‐lactams.…”
Section: Introductionmentioning
confidence: 99%